Efficacy of Colistin and Its Combination With Rifampin in Vitro and in Experimental Models of Infection Caused by Carbapenemase-Producing Clinical Isolates of Klebsiella pneumoniae - Pachón-Ibáñez, María E.; Labrador-Herrera, Gema; Cebrero-Cangueiro, Tania; Díaz, Caridad; Smani, Younes; del Palacio, José P.; Rodríguez-Baño, Jesús; Pascual, Alvaro; Pachón, Jerónimo; Conejo, M. Carmen (Frontiers in Microbiology, 2018)
Despite the relevance of carbapenemase-producing Klebsiella pneumoniae (CP-Kp) infections there are a scarce number of studies to evaluate in vivo the efficacy of combinations therapies. The bactericidal activity of colistin, rifampin, and its combination was studied (time–kill curves) against four clonally unrelated clinical isolates of CP-Kp, producing VIM-1, VIM-1 plus DHA-1(acquired AmpC β-lactamase), OXA-48 plus CTX-M-15 (extended spectrum β-lactamase) and KPC-3, respectively, with colistin MICs of 0.5, 64, 0.5, and 32 mg/L, respectively. The efficacies of antimicrobials in monotherapy and in combination were tested in a murine peritoneal sepsis model, against all the CP-Kp. Their efficacies were tested in the pneumonia model against the OXA-48 plus CTX-M-15 producers. The development of colistin-resistance was analyzed for the colistin-susceptible strains in vitro and in vivo. In vitro, colistin plus rifampin was synergistic against all the strains at 24 h. In vivo, compared to the controls, rifampin alone reduced tissue bacterial concentrations against VIM-1 and OXA-48 plus CTX-M-15 strains; CMS plus rifampin reduced tissue bacterial concentrations of these two CP-Kp and of the KPC-3 strain. Rifampin and the combination increased the survival against the KPC-3 strain; in the pneumonia model, the combination also improved the survival. No resistant mutants appeared with the combination. In conclusion, CMS plus rifampin had a low and heterogeneous efficacy in the treatment of severe peritoneal sepsis model due to CP-Kp producing different carbapenemases, increasing survival only against the KPC-3 strain. The combination showed efficacy in the less severe pneumonia model. The combination prevented in vitro and in vivo the development of colistin resistant mutants.